Relationship of the Functional States of the Thyroid and the Reproductive System in Women under Iodine Deficiency - Tokhirovna, Ergasheva Gulshan (Journal of Science in Medicine and Life, 2024)
Thyroid gland (thyroid) pathology is more common in women of reproductive age. The article presents a review of modern literature on the effect of autoimmune thyroiditis, thyroid hypo- and hyperfunction, as well as its structural changes on the reproductive system of women. Autoimmune aggression against thyroid cells is often associated with diseases of the reproductive system and is the most common cause of primary hypothyroidism. Key words: reproductive age, thyroid gland, thyroiditis, woman.